Copyright Protection for Songs and/or Music Remixes Published on YouTube - Melinda Wahyu Prihastiwi; Tashya Panji Nugraha (West Science Law and Human Rights, 2026)
Song recycling is the activity of updating and re-singing a singer's previous song (old version). Recycling songs and/or music generally used Youtube as a publication medium. The purpose of this study is to determine the copyright protection of song and/or recycling through Youtube media as a medium that is often used to publish song recycling content. This research uses normative juridical research methods. The results showed that based on Law No. 28 of 2014 concerning Copyright, everyone who wants to recycle songs must obtain permission from the creator and/ or copyright holder because it includes exercising economic rights belonging to the creator and/or copyright holder. Law No. 19 of 2016 concerning Amendments to Law No. 11 of 2008 concerning Electronic Information and Transactions also regulated that the recycled version of the song is one form of electronic document, if it contains copyright infringement then electronic system operator has the right to cut off access.